Ecología de interacciones de la araña lince verde, Peucetia viridans (Hentz) (Araneae: Oxyopidae), y la dominguilla, Croton ciliatoglanduliferus (Ortega: Euphorbiaceae), en una selva baja de Jalisco - Jiménez Salinas, Everardo (Universidad Autónoma Metropolitana, 2008)
The association of the Green Lynx spider, Peucetia viridans (Hentz: Oxyopidae), with Croton ciliatoglanduliferus (Ortega: Euphorbiaceae), or dominguilla as it is locally known, was analyzed in a tropical dry forest of Jalisco, in Western Mexico in 2004 and 2005. The ecological system involving the plant, its pollinators-herbivores and the Green Lynx spider was examined. The need of insect pollinators for the reproduction of the dominguilla shrub was evaluated. Height, foliage cover, number of inflorescences, number of male and female females as well as density were also assessed in order to consider their posible influence on the microhabitat selection by the spider. P. viridans completes its entire life cycle on C. ciliatoglanduliferus where it possibly takes advantage of the shelter it provides and the insects in attracts which are used as prey. The association between the floral visitors and herbivores and the plant could be controlled by the green lynx spider. This influence would decrease the plant´s reproductive success if the spider feeds on the pollinators. On the other hand, the plant could increase its success if the spider favours the herbivores, which feed on the leaves and flowers. Preliminary results show a significant negative association between the distribution of the spider and pollen collecting insects but a positive one with the herbivores that were exposed to the sun. In addition, the spider distribution had a negative association with temperature. In the early rainy season of 2004 P. viridians favoured higher (P<0.01) and number of inflorescences (P<0.05). The preference for plants with more inflorescences was then assessed by following the spider numbers during a three-week period in two groups of plants. The first one (n=50) was left untouched while all inflorescences were removed from the second (n=50). The spiders deserted plants from which inflorescences were eliminate (P<0.05). Nevertheless the association between C. ciliatoglanduliferus and P. viridans showed significant temporal variations with respect to different plant characteristics. In August 2005 I found two C. ciliatoglanduliferus patches, one with lynx spiders and the other with no spiders present. There were significantrly more male flowers in the first patch (P<0.01). One month later the pattern was repeated and the difference was even more evident (P<0.005). The comparison of plant density in patches with and without the Green lynx spider showed no significant differences buty a marginal trend suggested that those patches without the spider had more plants per unit área.; Se analizó la relación de la araña lince verde. Peucetia viridans (Hentz: Oxyopidae), con la dominguilla, Croton ciliatoglanduliferus (Ortega: Euphorbiaceae), en una selva baja caducifolia de Jalisco, México en 2004 y 2005. Se analizó la interacción entre la dominguilla, sus polinizadores, herbívoros y la araña lince. Asimismo, se evaluó la necesidad de polinizadores en la dominguilla. Se determinaron características físicas del crotón como altura, cobertura vegetal, número de inflorescencias, el número de flores masculinas y femeninas, así como densidad, para estimar la influencia de estas variables sobre el uso del hábitat de la araña lince. P. viridans completa la totalidad de su ciclo de vida en C. ciliatoglandulifers y hace uso y selección preferencial del hábitat en función de los beneficios obtenidos indirectamente de la planta. La dominguilla es una planta arbustiva que requiere de polinizadores para la producción de semillas. La asociación de los visitantes florales, insectos herbívoros y principalmente polinizadores, con la dominguilla podría estar mediada por la araña lince. En un análisis canónico de correspondencias se encontró una asociación significativa de las arañas lince con polinizadores colectando polen (-) y herbívoros tomando el sol (+), y con la temperatura ambiental (-). P. viridans mostró una preferencia por las plantas con mayor cobertura, número de inflorescencias y altura de las plantas al comienzo de la época de lluvias de 2004. Para probar si P. viridans era atraída por individuos de C. ciliatoglanduliferus con más inflorescencias, se suprimieron las inflorescencias a un lote de crotón. Se encontró que P. viridans desertó aquellas plantas en las que estuvieron ausentes las inflorescencias en comparación de las plantas que las mantuvieron. Sin embargo, la asociación entre C. ciliatoglanduliferus y P. viridans presentó variaciones temporales con relación a las características físicas de las plantas. En agosto 2005 se observó que la araña se distribuía en manchones en donde la planta tenía un mayor número de flores masculinas. Un mes después, se repitieron los conteos de flores y arañas y se obtuvieron los mismos resultados. La densidad del arbusto no fue significativamente diferente en la comparación de manchones de plantas con y sin arañas.